2012
DOI: 10.1155/2012/934571
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Preoperative Diagnosis of Ovarian Pregnancy with Transvaginal Scan

Abstract: Ovarian pregnancy is a rare variant of ectopic pregnancy, and an accurate preoperative diagnosis is very challenging. Dr. Saint Monnissey described the first reported case of ovarian pregnancy in 17th century. Transvaginal ultrasonography is a valuable tool in identifying an ovarian pregnancy from other types of ectopic pregnancies. Management with laparoscopy or laparotomy is required in all cases, and in almost all cases, ovary can be preserved since implantation is usually superficial (Koo et al.; 2011). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…The histopathology findings of squamous cell carcinoma as the most common type of cervical cancer in our study is similar to studies done in Kenya, Uganda and South Africa in which as high as 80% of cases had squamous cell carcinoma [ 13 , 16 - 18 ]. In contrast, the finding of non-squamous cervical cancer in this study of just 8.7% is lower than the 11% reported in Nigeria [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…The histopathology findings of squamous cell carcinoma as the most common type of cervical cancer in our study is similar to studies done in Kenya, Uganda and South Africa in which as high as 80% of cases had squamous cell carcinoma [ 13 , 16 - 18 ]. In contrast, the finding of non-squamous cervical cancer in this study of just 8.7% is lower than the 11% reported in Nigeria [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…5 Other risk factors for OEP include a history of endometriosis, ovulation induction and other assisted reproductive technologies, and advanced maternal age. 1,6,7 The clinical presentation of OEP is similar to other ectopic pregnancies, namely, mild-to-moderate pelvic pain, vaginal bleeding, abnormal beta-hCG levels, and a palpable adnexal mass. [6][7][8] The patient in this case had a few risk factors, including being of advanced maternal age and the use of ovulation induction medication.…”
Section: Discussionmentioning
confidence: 97%
“…1,6,7 The clinical presentation of OEP is similar to other ectopic pregnancies, namely, mild-to-moderate pelvic pain, vaginal bleeding, abnormal beta-hCG levels, and a palpable adnexal mass. [6][7][8] The patient in this case had a few risk factors, including being of advanced maternal age and the use of ovulation induction medication. Differential diagnoses of an OEP can include a corpus luteum cyst, a hemorrhagic ovarian cyst, appendicitis, tubal ectopic, or an early or failed intrauterine pregnancy (IUP).…”
Section: Discussionmentioning
confidence: 97%
“…Comstock et al, observed ultrasonography of six ovarian pregnancy patients and concluded the presence of hypoechoic ring on or within the surface of ovary in five out of six patients. 13 Corpus luteum and ovarian pregnancy are differentiated on the basis of echogenocity of hypoechoic ring. The corpus luteum appears less echogenic than rest of ovary while the ovarian pregnancy is more echogenic than rest of the ovary.…”
Section: Discussionmentioning
confidence: 99%